2024
DOI: 10.1007/s00784-024-05644-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved recurrence rates and progression-free survival in primarily surgically treated oral squamous cell carcinoma – results from a German tertiary medical center

Ann-Kristin Struckmeier,
Mayte Buchbender,
Rainer Lutz
et al.

Abstract: Objectives This study aimed to explore survival and recurrence patterns in patients undergoing primarily surgical treatment for oral squamous cell carcinoma (OSCC) at a high-volume tertiary medical center in Germany. Materials and methods The study included 421 patients with primary OSCC who underwent radical tumor resection, neck dissection, and reconstruction with a free flap. Prognostic relevance of clinicopathological characteristics was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Struckmeier et al in Germany reported that Recurrence manifested in 16.63% of the patients, encompassing local recurrence in (77.14% of the patients and distant metastasis in (34.28%). Neck recurrence occurred in only (0.24%) on the contralateral side [ 50 ]. Dysplastic cells need time to become malignant, hence close margins (47.8%) had greater recurrence than dysplastic margins (22.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Struckmeier et al in Germany reported that Recurrence manifested in 16.63% of the patients, encompassing local recurrence in (77.14% of the patients and distant metastasis in (34.28%). Neck recurrence occurred in only (0.24%) on the contralateral side [ 50 ]. Dysplastic cells need time to become malignant, hence close margins (47.8%) had greater recurrence than dysplastic margins (22.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Kernohan et al (2010) identified an 18% 2-year survival rate for patients who recurred within 3 months postoperatively [ 7 ]. Struckmeier et al reported that the 5-year Overall Survival stood at 58.29%, Patients with early recurrence within ≤ 12 months showed the least favorable prognosis [ 50 ]. This study found a 4% (2-years) survival rate and 32-month post-recurrence mortality.…”
Section: Discussionmentioning
confidence: 99%